Development of an Assessment Instrument for Conceptual Understanding, Collaboration Skills, and Learning Motivation on Gas Kinetic Theory - Siti Rahmatia; Yusman Wiyatmo; Edi Istiyono (Jurnal Penelitian Pembelajaran Fisika, 2025)
This study aims to develop an assessment instrument on the Kinetic Theory of Gases (Boyle's Law) to measure the conceptual understanding, collaboration skills, and learning motivation of high school students in the context of the Independent Curriculum. The instrument developed consists of 10 multiple-choice questions to measure conceptual understanding and 10 questionnaire statements for collaboration skills and learning motivation. The development process follows systematic stages, including planning, expert validation, and empirical trials. Content validity was analyzed using the Aiken V index, and it was found that all items were in the high validity category. Empirical validation was carried out using the Rasch model through Winsteps software, which showed that most items were in the statistical range of feasibility (Infit MNSQ: 0.80–1.15 for conceptual understanding, 0.85–1.13 for collaboration, and 0.82–1.12 for motivation). The reliability coefficient ranged from 0.74 to 0.85, indicating high internal consistency. The distribution of the level of difficulty of conceptual understanding questions includes easy (30%), moderate (40%), and complex (30%), thus reflecting balance. As many as 9 out of 10 conceptual understanding questions were declared valid and feasible, while all items in the collaboration and motivation questionnaire were maintained. These results indicate that the developed instrument is valid and reliable as a holistic assessment tool in physics learning, supports the formative assessment that aligns with 21st-century competencies, and strengthens collaborative character and lifelong learning motivation.